A Matlab toolbox implementing MSCG computation. Issue 28 (2022) - Basile, F.; Ferrara, L.
Abstract: Modified State Class Graph collects in a compact form the main information on all the possible evolutions of a given labeled TPN system initialized at a given marking. Recently, it has been used to solve different problems, in particular supervisor control synthesis, state estimation and system validation. It employs a symbolic characterization of the firing time intervals of the enabled transitions. This paper presents a set of MATLAB functions implementing the computation of MSCG in different ways, useful for applications.